Transformasi Pemasaran Digital UMKM Karang Taruna di Desa Sigara-Gara melalui Penyuluhan dan Pelatihan Online Selling - Putri Gami, Emelia Rahmadany; Harahap, Nur'ain; Mauliza, Sri; Munawaroh Harahap, Wilda Sri (CV. Devi Tara Innovations, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting regional economic development. However, many MSME actors in Sigara-Gara Village, Patumbak District, Deli Serdang Regency still rely on conventional marketing methods due to low digital literacy, limited content creation skills, and difficulties in utilizing e-commerce platforms. This community service program aimed to provide outreach and training on digital marketing, focusing on branding awareness, social media utilization, and e-commerce account setup and operation. The activity involved 15 MSME participants and was conducted using an andragogical approach emphasizing practice-based learning. The results indicate an improvement in participants’ understanding of digital marketing concepts and an increased motivation to shift from conventional to digital systems. Continued support and mentoring are recommended to ensure sustainable implementation of the acquired skills.